RECONFIGURABLE ANTENNA FOR WIRELESS COMMUNICATION SYSTEM - Mohamad Kamal A. Rahim, editor 524423; Farid Zubir, 1985-, editor 501013; Mohamad Kamal A. Rahim, contributor 524423; Farid Zubir 1985-, contributor 501013; Abdul Halim Dahalan, contributor 652197; Amier Hafiezun Abd. Rashid, contributor 652198; Badrul Hisham Ahmad, contributor 449782; Chan, Wei Yi, contributor 652199; Huda A. Majid, contributor 247154; Izni Husna Idris, 1989-, contributor 583754; Kamilia Kamardin, 1982-, contributor 569399; Marlina Ramli, contributor 652201; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2023)
Includes bibliographical references and index.